Lepromatous leprosy with dermatofibroma features: colonization or morphological variant of histoid leprosy with epidermal induction? - Outi Pontes, Cinthia Maria; Lourenco Pontes, Alexandre Lizardo; Ocanha-Xavier, Juliana Polizel [UNESP]; Xavier-Júnior, José Cândido Caldeira [UNESP] (Wiley, 2022)
Background: Leprosy is one of the main health problems in developing countries. It can show many different clinical presentations. Case report: A 37-yr-old woman with multiple reddish-brown papules on the lower and upper limbs, including the palms. The initial clinical impression was pityriasis lichenoides chronica. Biopsies were taken. The specimen from the left shin showed classical histological features of lepromatous leprosy. The specimen from the left thigh was similar to lipidized dermatofibroma showing epidermal hyperplasia with basal layer hyperpigmentation, a narrow Grenz zone, and spindle xanthomatous cells among dermal fibers. Fite-Faraco staining revealed many bacilli. Discussion: No matter the clinical presentation, in the presence of lipidized macrophages, Fite-Faraco staining (an inexpensive method available worldwide) should be performed to rule out leprosy, even in nonendemic areas or associated with a tumor.